Clinicopathologic Significance and Prognostic Value of Programmed Cell Death Ligand 1 (PD-L1) in Patients With Hepatocellular Carcinoma: A Meta-Analysis - Li, Jing-Hua; Ma, Wei-Jie; Wang, Gang-Gang; Jiang, Xiang; Chen, Xi; Wu, Long; Liu, Zhi-Su; Zeng, Xian-Tao; Zhou, Fu-Ling; Yuan, Yu-Feng (Frontiers in Immunology, 2018)
Background: The clinicopathological and prognostic significance of programmed cell death ligand 1 (PD-L1) expression in patients with hepatocellular carcinoma (HCC) remains controversial. Here, we undertook this meta-analysis to investigate the potential value of PD-L1 in HCC. Method: We searched databases like MEDLINE, EMBASE and Google Scholar for relevant studies published in English up to February 13, 2018. Eligible studies were evaluated by selection criteria. Hazard ratio (HR) and its 95% confidence interval (95% CI) were used to estimate the prognostic role of PD-L1 for overall survival (OS), disease-free survival (DFS) and recurrence-free survival (RFS). Odds ratio (OR) and the corresponding 95% CI were calculated to assess the relationship between PD-L1 and clinicopathological features. Publication bias was tested. Results: A total of 13 studies published from 2009 to 2017 were included in this meta-analysis, involving 1,843 patients with HCC. The results indicated that high PD-L1 could predict shorter OS (HR=1.57, 95% CI: 1.09-2.27, P<0.00001) as well as poorer DFS (HR=2.07, 95% CI: 1.20-3.58, P=0.009). Additionally, high PD-L1 expression was correlated to liver cirrhosis (OR=1.66, 95% CI: 1.10-2.50, P=0.02), poorer tumor BCLC stage (OR=0.30, 95% CI: 0.10-0.88, P=0.03) and portal vein invasion (OR=1.96, 95% CI: 1.04-3.68, P=0.04), but had no correlation with age, gender, tumor size, number of tumors, AFP, vascular invasion, HBVs-Ag, Anti-HCV, differentiation or TNM stage. In addition, no significant publication bias was found among these identified studies. Conclusion: This study revealed that overexpression of PD-L1 was predictive for worse OS and DFS in HCC. Furthermore, PD-L1 expression was associated with liver cirrhosis, portal vein invasion, and BCLC stage.